The Effectiveness of Priority Prolegnas in the Development of Quality Law in Indonesia - Satria, Eko; Mozin, Nopiana; Nur, Al Hiday (Jambura Journal Civic Education, 2025)
This study aims to evaluate the extent to which the National Legislation Program (Prolegnas) Priority is able to achieve the legislative formation targets in terms of both quantity and quality for the period 2015 to 2029. As a planning instrument for national legislation, Prolegnas is expected to serve as a foundation for creating a legal system that is harmonious, effective, and responsive to the needs of society. However, in practice, the implementation of Prolegnas often falls short of expectations. This research employs a normative legal method with statutory and conceptual approaches, and the data are analyzed using a descriptive qualitative technique. The data sources include official Prolegnas documents, legislative performance reports, and relevant academic studies. The findings indicate that the success rate of the Priority Prolegnas in recent legislative periods has ranged only between 13% and 20% of the established targets. This reflects a discrepancy between planning and legislative realization. Several key inhibiting factors include sectoral egos among legislative and executive institutions, low public participation in the legislative process, weak synchronization and harmonization of regulations, and a lack of post-enactment evaluation of legislation. The study concludes that there is a pressing need for more realistic and measurable legislative planning, stronger public engagement, and improved legal substance quality. Prolegnas should not only focus on the quantity of legislation but also prioritize the quality of regulations in order to produce fair, relevant, and effective laws that respond to the dynamic needs of society.